A computational study on possible active species in nickel(II)-catalyzed 1-butene dimerization in [BMIM](+)[AlCl4](-) ionic liquid solution - Görling, Andreas; Hieringer, Wolfgang; Nikiforidis, Ioannis (Journal of Coordination Chemistry, 2015)
The butene insertion step of nickel complex-catalyzed butene dimerization in the presence of a [BMIM](+)[AlCl4](-) ionic liquid has been studied using density functional theory. The possibility of anion coordination from the ionic liquid to the catalyst complex has explicitly been taken into account. The calculated relative energies of various possible active catalyst complexes suggest that anion coordination to the nickel center may be thermodynamically favorable. Phosphine-free complexes which are only coordinated by one or two AlCl4- anions are higher in energy and show higher activation barriers for butene insertion. The lowest activation barrier has been found for a mono-phosphine nickel complex. Explanations for the calculated barriers based on structural data are offered.
Keywords: Olefin dimerization; Olefin insertion; Homogeneous catalysis; Density functional theory; Computational chemistry